Static and Dynamic Behavior of Circularized Reinforced Concrete Columns Strengthened with Hybrid CFRP - Abdulghafoor, Z. H.; Al-Baghdadi, H. A. (Engineering, Technology & Applied Science Research, 2022)
In this study, three strengthening techniques, near-surface mounted NSM-CRFP, NSM-CFRP with externally bonding EB-CFRP, and hybrid CFRP with circularization were studied to increase the seismic performance of existing RC slender columns under lateral loads. Experimentally, 1:3 scale RC models were studied and subjected to both lateral static load and seismic excitation. In the dynamic test, a model was subjected to El Centro 1940 NS earthquake excitation by using a shaking table. According to the test results, the strengthening techniques showed a significant increase in load carrying capacity, of about 86.6%, and 46.6%, for circularization and NSM-CFRP respectively, of the reference unstrengthened columns. On the other hand, columns strengthened with hybrid NSM-CFRP and EB-CFRP showed a different failure mode. Dynamically, the lateral drift was decreased by about 75%, 47%, and 49% for earthquake amplitudes of 0.05g, 0.15g, and 0.32g respectively. Finally, it was concluded, depending on the static and dynamic analyses, that the circularization process showed a significant increase in lateral load-bearing capacity.